2023
DOI: 10.1002/pds.5590
|View full text |Cite
|
Sign up to set email alerts
|

Is anticholinergic and sedative drug burden associated with postdischarge institutionalization in community‐dwelling older patients acutely admitted to hospital? A Norwegian registry‐based study

Abstract: Purpose Investigate the association between anticholinergic (AC) and sedative (SED) drug burden before hospitalization and postdischarge institutionalization (PDI) in community‐dwelling older patients acutely admitted to hospital. Methods A cross‐sectional study using data from the Norwegian Patient Registry and the Norwegian Prescription Database. We studied acutely hospitalized community‐dwelling patients ≥70 years during 2013 (N = 86 509). Patients acutely admitted to geriatric wards underwent subgroup anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Full‐text articles were sought and screened for 316 articles that appeared to meet the inclusion criteria. Seventy studies 6,13–81 were included in the systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full‐text articles were sought and screened for 316 articles that appeared to meet the inclusion criteria. Seventy studies 6,13–81 were included in the systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The details of the included studies are summarized in Supplementary Table S1. There were 65 studies conducted in humans 6,13–76 and five in animals (mice) 77–81 . Of the studies conducted in humans, there were 38 cross‐sectional studies, 14 retrospective cohort studies, 11 prospective cohort studies, one case–control study, and one mixed prospective/retrospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies from all around the world showed significant variations in prevalence rates of anticholinergic effects exposure. ( Cebron Lipovec et al, 2020 , Cross et al, 2016 , Havnes et al, 2023 , Mantri et al, 2019 , Mayer et al, 2017 , Salahudeen et al, 2015b , Tristancho-Perez et al, 2021 ). This significant difference in our study regarding anticholinergic burden prevalence could be due to many factors, including first, the utilization of a newer anticholinergic burden scale (CALS) where the list of potential anticholinergic drugs contains 217 drugs ( Ramos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%